Application du modèle d’apprentissage coopératif du type Snowball Throwing à l’expression orale dans la classe XI-E de SMA Sedes Sapientiae - Muhammad Faris Adilah; Aisyiah Al Adawiyah (Universitas Negeri Semarang, 2026)
Among the four language skills, oral expression is one of the most difficult to master. The students of class XI-E face difficulties in pronouncing words in French and do not yet possess sufficient vocabulary to express themselves properly. This is evident when they are unable to answer the teacher’s questions during the lesson. The cooperative learning model Snowball Throwing is considered appropriate for meeting oral expression needs in this class. This research aims to describe the implementation of this model in French language teaching, particularly to develop students’ oral competence in class XI-E at SMA Sedes Sapientiae. It is a descriptive qualitative study, using the Miles and Huberman analysis model. The data were collected from an oral expression test administered after the model was applied. The results show that 10 students (about 53%) reached the mastery criterion, while 9 students (about 47%) did not. The study includes 12 steps in a single application session. These results indicate that the Snowball Throwing model has a positive impact on improving oral production in French, although further support or adaptation is still needed to optimize the results at the class level.